Does acqui-hiring pay off? An empirical investigation of founder retention - Nikolaus Seitz; Erik E. Lehmann (Small Business Economics, 2025)
In the fiercely competitive global talent landscape, even tech giants struggle to attract and retain top-tier entrepreneurial talent. To address this challenge, companies increasingly employ acqui-hiring—a strategic approach based on mergers and acquisitions aimed at acquiring startups primarily for their human capital. However, empirical evidence supporting the effectiveness of acqui-hiring is limited and contentious. Our study aims to fill this gap by investigating the retention decisions of acqui-hired founders, who are central to the success of such acquisitions. Leveraging a dataset comprising 454 acqui-hired founders from 241 transactions by Google and Meta (Facebook), our findings highlight the difficulty of retaining individual entrepreneurs compared to entire co-founder teams, and underscore the importance of maintaining co-founders' hierarchy. Our research contributes to the strategic entrepreneurship literature by exploring nuanced organizational design decisions in intrapreneurship and startup–corporate collaborations, shedding light on the efficacy of structural integration for knowledge and innovation transfer.
Keywords: D22; L11; L26; 330; Acqui-hiring; Technology merger and acquisitions; Turnover prediction; Founder retention